2021
DOI: 10.1093/jn/nxab135
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Disrupted Provision and Utilization of Health and Nutrition Services in Uttar Pradesh, India: Insights from Service Providers, Household Phone Surveys, and Administrative Data

Abstract: Background The coronavirus (COVID-19) pandemic may substantially affect health systems, but little primary evidence is available on disruption of health and nutrition services. Objectives This study aimed to 1) determine the extent of disruption in provision and utilization of health and nutrition services induced by the pandemic in Uttar Pradesh, India; and 2) identify how adaptations were made to restore service provision i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…Results of many studies have shown that a balanced diet is crucial for building a stronger immune system and reducing the risk of infectious diseases [ 40 , 41 ]. Notwithstanding, previous studies [ 42 , 43 ], as well as the results of this study, show that unfortunately after the Covid-19 pandemic the rate of routine nutrition consultations and the provision of appropriate nutritional programs to patients referred to PHC centers, decreased noticeably. The reason for this could be the unknown treatment process of Covid-19 disease at the beginning of the outbreak and the role of nutritional interventions in the treatment of disease, fear of pandemic virus infection, corona restrictions applied by the government to reduce and prohibit traffic and quarantine.…”
Section: Discussioncontrasting
confidence: 47%
“…Results of many studies have shown that a balanced diet is crucial for building a stronger immune system and reducing the risk of infectious diseases [ 40 , 41 ]. Notwithstanding, previous studies [ 42 , 43 ], as well as the results of this study, show that unfortunately after the Covid-19 pandemic the rate of routine nutrition consultations and the provision of appropriate nutritional programs to patients referred to PHC centers, decreased noticeably. The reason for this could be the unknown treatment process of Covid-19 disease at the beginning of the outbreak and the role of nutritional interventions in the treatment of disease, fear of pandemic virus infection, corona restrictions applied by the government to reduce and prohibit traffic and quarantine.…”
Section: Discussioncontrasting
confidence: 47%
“…Another study leveraged a context of an intervention to strengthen nutrition services through a government antenatal care platform in Uttar Pradesh, India. The study demonstrated a steep reduction in service provision (40–80 pp) and utilization (40–80 pp) during lockdowns and a gradual recovery in the implementation scale in later 2020 ( 26 ). Maternal, infant, and young child nutrition counseling services in urban health facilities in Bangladesh experienced a reduction in the service provision in anthropometric monitoring and child immunizations for pregnant women (20–29 pp) and children (37–57 pp) ( 10 ).…”
Section: Discussionmentioning
confidence: 93%
“…Children and adolescents experienced an unusual interruption in their everyday lives that included prolonged stay within home, altered relationship dynamics with their caregivers and family members, less-frequent interactions with peers and relatives, lack of access to outdoor activities, changed nutritional and lifestyle behaviors and other changes at the household level [59, 60]. These problems compounded the effects of community and social changes associated with this pandemic, which included social distancing, closure of schools and institutions, and interruption of health and social services [54, 61, 62]. Lastly, universal challenges such as socioeconomic problems and health hazards of COVID-19 impacted children, adolescents, and their families that also affected mental health and wellbeing [5, 47, 63].…”
Section: Discussionmentioning
confidence: 99%